The use of reactive strength index-modified as an explosive performance measurement in male and female athletes - Suchomel, T. J.; Bailey, C. A.; Sole, C. J.; Grazer, J. L.; Beckham, G. K. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
This study examined the reliability of reactive strength index-modified (RSImod), relationships between RSImod and force-time variables, and difference in RSImod between male and female collegiate athletes. 106 Division I collegiate athletes performed unloaded and loaded countermovement jumps. Intraclass correlation coefficients and coefficients of variation were used to establish the reliability of RSImod. Correlations were calculated between RSImod and rate of force development, peak force, and peak power. RSImod appears to be a reliable performance measurement in male and female athletes. Furthermore, RSImod has moderate to very large relationships with rate of force development, peak force, and peak power. Statistically significant differences in RSImod existed between males and females during both unloaded and loaded CMJs.